Effect of Whole-body Vibration Combined with Task Oriented Training on Muscle Strength, Balance, and Gait in Stroke Patients with Hemiplegia: A Pilot Randomized Controlled Trial - Choi, Kwang-Yong; Kim, Jung-Hee; Lee, ByoungHee (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2020)
The current study aimed to evaluate the effects of whole-body vibration combined with task-oriented training on muscle strength, balance, and gait in stroke patients with hemiplegia. In total, 24 stroke patients were included in this study. All participants were randomly assigned to either the whole-body vibration combined with task-oriented training group (n=12) or the whole-body vibration group (n=12). The WBVMT group underwent training (8 sets) for 30 min a day, 5 times per week for 4 weeks. Meanwhile, the WBV group underwent training (8 sets) for 30 min a day, 5 times per week for 4 weeks. Both groups received standard rehabilitation physical therapy for 60 min a day, 5 times a week for 4 weeks. In all participants, the scores for the hip extensor (HE) and knee extensor (KE) muscle strength, Five Times Sit-to-Stand (FTSTS) Test, limit of stability (LOS), Timed Up and Go (TUG) Test, Berg Balance Scale (BBS), 10-Meter Walk Test (10MWT), and 6-Min Walk Test (6MWT) were evaluated before and after the intervention. The WBVMT and WBV groups had a significant increase in the scores for HE and KE strength, FTSTS test, LOS, TUG test, BBS, 10MWT, and 6MWT (p<0.05). In particular, the WBVMT group had a significantly greater improvement than the WBV group in terms of KE muscle strength and TUG test, BBS, 10MWT, and 6MWT scores (p<0.05). WBVMT improved muscle strength, balance, and gait in stroke patients with hemiplegia.
Keywords: stroke; whole-body vibration; task-oriented approach; muscle strength; balance; gait